Knowledge, Attitudes and Practices regarding Long-Term Complications of COVID-19 among a Sub-Urban Population in Sri Lanka - Witharana, C.; Siridewa, K.; Weerasinghe, M.; Karunathilake, I.M. (International Journal of Medical Research & Health Sciences, 2021)
Background: Recently, a surge of COVID 19 was observed globally, regionally, and nationally. With increasing numbers of cases, the frequency of long COVID is on the rise. Management and control of long COVID depend on changes in respect of human behaviours and require an understanding of Knowledge, Attitudes, and Practices (KAP) regarding health threats. Methods: A descriptive cross-sectional study using an online survey to gather data on the socio-economic background, knowledge, attitudes, and practices on long-term complications of COVID. Results: Out of 201 respondents, 89.2% of participants have heard about long-term complications of COVID 19. Only 35.9% have demonstrated adequate knowledge in the questions relating to co-morbidities and risk factors of COVID-19. A total of 92.2% believe that they should adhere to preventive measures following vaccination. Less than 60% were following the advice on avoiding unnecessary travel and crowded places. Further, less than 50% were following COVID preventive measures. Conclusion: Although the majority of participants have heard about long-term complications and common symptoms, the knowledge regarding co-morbidities that can lead to severe disease and long COVID was not satisfactory. The attitudes of the participants indicated increasing concern about long COVID. Practices indicate a lack of adherence to key measures such as avoiding crowded places. These findings highlight the need for further increasing of awareness
Keywords: Long COVID; COVID-19 vaccination; COVID awareness